Prevalence of clinically significant liver disease within the general population, as defined by non-invasive markers of liver fibrosis: a systematic review - Harris, Rebecca; Harman, David J.; Card, Timothy R.; Aithal, Guruprasad P.; Guha, Indra Neil (Elsevier, 2017)
At present, there is no evidence based pathway to stratify risk of chronic liver disease in a general population setting. Non-invasive tests of liver fibrosis may provide a mechanism for earlier diagnosis. These tests have been extensively validated in the hospital setting but their performance in a general population setting is unclear. We performed a systematic review of non-invasive tests used to stratify patients at risk of clinically significant liver disease in a general population setting and report the prevalence of chronic liver disease as defined by these tests. We systematically searched EMBASE, MEDLINE, Web of Science, reference lists from the original studies and recent conference proceedings. All study designs were considered. Nineteen studies were identified, utilising eleven non-invasive tests. Only transient elastography and Fibrotest were compared against histological end-points. The prevalence of liver fibrosis varied between 0.7% and 25.7%. More focussed stratification for advanced liver fibrosis (0.9%-2%) or cirrhosis (0.1%-1.7%) narrowed estimates of prevalence. Studies targeting patients with liver disease risk factors such as hazardous alcohol use or type 2 diabetes reported higher prevalence of advanced liver fibrosis (0%-27.9%) and cirrhosis (2.4%-4%). Validated non-invasive tests of liver fibrosis consistently detected otherwise unrecognised liver disease in the general population. Studies targeting risk factors found cirrhosis in 2.4 to 4 % of their target populations. Reliance on abnormal liver function tests will miss the majority of patients with significant liver injury. New pathways to stratify chronic liver, using non-invasive markers of liver fibrosis, are needed in the general population setting.